Social Carrying Capacity Kawasan Pariwisata Super Premium Marina Labuan Bajo - Da-Costa, William (Journal of Tourism and Hospitality Analysis (JoTHA), 2024)
Social carrying capacity is related to the local community's acceptance towards tourism and its tourists.  Labuan Bajo, especially in the Marina Area, is one of the tourism areas approved as a super-premium area.  Herewith, it gives the impact and pressure to the local community. Therefore, this research aimed to determine the social carrying capacity of the Marina Labuan Bajo area. This research collected data by spreading the questionnaire to 5 villages in this area. The questionnaire, which contained 33 questions, was given to 100 respondents. The sample collection technique used in this research is proportional sampling, which is analyzed using descriptive statistics. The result shows that the social carrying capacity in the Marina Labuan Bajo area has not been exceeded. The local community still accepts and never refuses tourism. The results above strengthen the argument that local people feel more positive than negative impacts from the development of super premium tourism in the Marina Area.